2011
DOI: 10.1210/en.2011-1008
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Release of Corticosteroid-Binding Globulin from the Liver Restrains the Glucocorticoid Hormone Response to Acute Stress

Abstract: A strict control of glucocorticoid hormone responses to stress is essential for health. In blood, glucocorticoid hormones are for the largest part bound to corticosteroid-binding globulin (CBG), and just a minor fraction of hormone is free. Only free glucocorticoid hormone is able to exert biological effects, but little is known about its regulation during stress. We found, using a dual-probe in vivo microdialysis method, that in rats, the forced-swim stress-induced rise in free corticosterone (its major gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 55 publications
3
74
1
2
Order By: Relevance
“…Interestingly, we did not find such a stress-induced, MR-dependent enhancement of amygdala activity in the task directly following stressor onset (Vogel et al, 2015b). This might suggest that the stress-induced enhancement of amygdala activity might take about twenty minutes to arise which would be in line with in-vitro findings of enhanced amygdala excitability after corticosterone applications of 20 min (Karst et al, 2010) and a delayed rise of brain corticosterone levels after stress (Qian et al, 2011). Furthermore, the stress-induced increase in amygdala activity and connectivity may be transient as amygdala activity was found to be reduced one hour after hydrocortisone administration (Henckens et al, 2010) and no connectivity increase with the striatum could be detected one hour after stress onset (van Marle et al, 2010) or hydrocortisone administration (Henckens et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, we did not find such a stress-induced, MR-dependent enhancement of amygdala activity in the task directly following stressor onset (Vogel et al, 2015b). This might suggest that the stress-induced enhancement of amygdala activity might take about twenty minutes to arise which would be in line with in-vitro findings of enhanced amygdala excitability after corticosterone applications of 20 min (Karst et al, 2010) and a delayed rise of brain corticosterone levels after stress (Qian et al, 2011). Furthermore, the stress-induced increase in amygdala activity and connectivity may be transient as amygdala activity was found to be reduced one hour after hydrocortisone administration (Henckens et al, 2010) and no connectivity increase with the striatum could be detected one hour after stress onset (van Marle et al, 2010) or hydrocortisone administration (Henckens et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…FS and RS are strong stressors, resulting in high glucocorticoid responses, whereas NE is regarded as a mild psychological stressor, leading to moderate increases in plasma hormone levels (16). MR binding to GREs was very similar after the different stressors, albeit with consistent intergene differences.…”
Section: Discussionmentioning
confidence: 88%
“…The peak in GR binding at 30 min after stress concurs with the peak in stress-induced plasma glucocorticoid levels, but in view of recent findings on stress-induced free CORT levels (16), this finding was unexpected. Recent microdialysis studies in vivo have shown that, after FS stress, the peak in free CORT in the hippocampus is delayed 20-30 min compared with the plasma hormone response (16,25). Thus, because the free CORT concentration is the critical parameter for hormone-receptor interaction, maximal GR binding to GREs after stress would be expected to occur at 60 min rather than at 30 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, CBG levels can either increase or decrease in response to acute or chronic stress (Alexander and Irvine, 1998;Boonstra, 2005;Davenport et al, 2008;Delehanty and Boonstra, 2009;Qian et al, 2011). Thus, the interpretation of changes in cortisol levels in response to stress would benefit from including both free and total forms of the hormone as well as reporting changes in CBG concentrations.…”
Section: Limits To Using Hpa Axis Activity As An Indication Of Animalmentioning
confidence: 99%